2016
DOI: 10.1016/j.brat.2016.05.006
|View full text |Cite|
|
Sign up to set email alerts
|

Take a look at the bright side: Effects of positive body exposure on selective visual attention in women with high body dissatisfaction

Abstract: Women with high body dissatisfaction look less at their 'beautiful' body parts than their 'ugly' body parts. This study tested the robustness of this selective viewing pattern and examined the influence of positive body exposure on body-dissatisfied women's attention for 'ugly' and 'beautiful' body parts. In women with high body dissatisfaction (N = 28) and women with low body dissatisfaction (N = 14) eye-tracking was used to assess visual attention towards pictures of their own and other women's bodies. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 23 publications
2
43
3
Order By: Relevance
“…Another possibility is that these attentional biases reflect theorized selective attention for goal performance information for women with appearance goals to be “beautiful” (Fairburn et al, ). Such explanations correspond with findings that women with eating disorders and body dissatisfaction tend to focus on attractive regions of others' bodies (Blechert et al, ; Glashouwer et al, ; Jansen et al, ; Roefs et al, ; Smeets et al, ) and attractive rather than unattractive bodies (Cho & Lee, ). In comparison, thoughts pertaining to the self, as reflected in a bias for negative‐appearance words, might not be as accessible in underlying appearance schemas when cueing with images of thin models.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Another possibility is that these attentional biases reflect theorized selective attention for goal performance information for women with appearance goals to be “beautiful” (Fairburn et al, ). Such explanations correspond with findings that women with eating disorders and body dissatisfaction tend to focus on attractive regions of others' bodies (Blechert et al, ; Glashouwer et al, ; Jansen et al, ; Roefs et al, ; Smeets et al, ) and attractive rather than unattractive bodies (Cho & Lee, ). In comparison, thoughts pertaining to the self, as reflected in a bias for negative‐appearance words, might not be as accessible in underlying appearance schemas when cueing with images of thin models.…”
Section: Discussionsupporting
confidence: 81%
“…Second, there were correlations between poorer body image and attentional biases for positive-appearance words in both the appearance-cued and time-delayed DPTs. Given that past research has found similar attentional biases between women with body dissatisfaction and eating disorders (Aspen et al, 2013;Blechert et al, 2010;Gao et al, 2011;Glashouwer et al, 2016;Jansen et al, 2005), it could be speculated that women with body dissatisfaction who possess these biases may be at particular risk for development of clinical disorders. Further investigation of attentional biases for positive-valence stimuli in experimental and longitudinal studies would help address their theorized causal and maintenance role in these disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have utilized eye‐tracking to investigate the processing of body‐ and/or food‐related stimuli, primarily for body or weight dissatisfaction in non‐clinical samples (e.g., Gao et al, ; Glashouwer, Jonker, Thomassen, & de Jong, ; Jansen, Nederkoorn, & Mulkens, ). For instance, despite self‐reported improvement of reduced shape concern and eating disorder symptoms, Glashouwer et al () reported that women with high body dissatisfaction attended to “ugly” body parts longer than “beautiful” ones for both their own and other people's body images, after a 5‐week body positivity training. Thus, it may be the case that eye‐tracking is a more sensitive objective measure than self‐report.…”
Section: Introductionmentioning
confidence: 99%
“…. For instance, despite self-reported improvement of reduced shape concern and eating disorder symptoms, Glashouwer et al (2016) reported that women with high body dissatisfaction attended to "ugly" body parts longer than "beautiful" ones for both their own and other people's body images, after a 5-week body positivity training. Thus, it may be the case that eyetracking is a more sensitive objective measure than self-report.…”
mentioning
confidence: 99%